HUBUNGAN PENGETAHUAN KODE ETIK KEDOKTERAN INDONESIA DENGAN SIKAP DOKTER TERHADAP WITHHOLDING LIFE SUPPORT THERAPI DO NOT RESUSCITATE ATAS PERMINTAAN PASIEN - Putri Nabilla Febrianty, (2023)
Do Not Resuscitate (DNR) is a medical instruction given at patient's request to withhold cardiopulmonary resuscitation (CPR) in cardiac arrest. This action represents an example of withholding life support and raises ethical issues for doctors in Indonesia as it contradicts the Indonesian Medical Code of Ethics, particularly Article 17, which obligates doctors to provide care to emergency patients. This study was conducted to determine the relationship between knowledge of the Indonesian Medical Code of Ethics and doctors' attitudes towards the Do Not Resuscitate (DNR) order. The study utilized an analytical observational design with a cross-sectional approach, conducted between May 2023 and June 2023 at the office of the Indonesian Medical Association in Depok. The research sample consisted of 38 members of the Indonesian Medical Association in Depok, selected using consecutive sampling based on inclusion and exclusion criteria. Data analysis was using chi-square and Fisher's exact tests. The majority of respondents had good knowledge, with a total of 31 individuals (81.6%), and high attitudes, with a total of 26 individuals (68.4%). The results of the data analysis indicated a p-value of 0.176, which means there is no relationship between knowledge level and doctors' attitudes towards the Do Not Resuscitate (DNR) order.